The Prospects of Using Fuzzy Approaches to Ecological Risk Assessment (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The issue of environmental quality improvement has been receiving much attention in the developed countries in recent years. Due to that, the role of assessment of ecological risks associated both with natural events and technogene activity of humans is increasing. Previous approaches to the assessment of ecological risks were fully based on statistical data and expert evaluation of potential losses and probabilities of unfavourable consequences. When this kind of assessment is carried out, it is assumed explicitly that experts are able to evaluate point probabilities. However, such assumptions are far from being true. As a result, fuzzy approaches to ecological risk assessment became popular lately. This paper focuses on two practical approaches of that kind. The paper is aimed at attracting practical attention to new up-to-date techniques that could be successfully applied to assess ecological risks in Latvia.